A randomized clinical trial of unfractioned heparin for treatment of sepsis (the HETRASE study): design and rationale [NCT00100308] (2006)
ABSTRACT: Introduction: Infection promotes coagulation via a large number of molecular and cellular mechanisms, and this procoagulant activity has boosted basic and clinical research using anticoagulant molecules as therapeutic tools in sepsis. Heparin, which is a naturally occurring proteoglycan that acts by reducing thrombin generation and fibrin formation, has not been rigorously tested in a randomized clinical trial. Methods: Randomized, double-masked, placebo-controlled, single-center clinical trial. Patients are recruited through the emergency room at Hospital Universitario San Vicente de Paul. This is a 650-bed University Hospital in Medellín, Colombia and is a referral center for a region with approximately 3 million habitants. The recruitment process started on July 2005 and will finish on June 2007. Patients aged 18 years or older, males or females, hospitalized with clinically or microbiological confirmed sepsis, have been included. The interventions are unfractioned heparin in low dose continuous infusion (500 units per hour for 7 days) or placebo, additionally to the standard of care for sepsis patients in Colombia. Results: Our primary aims are to estimate the effects of heparin on hospital length of stay and change from baseline Multiple Organ Dysfunction (MOD) score. Secondary objectives are to estimate the effects of heparin on 28-day all-cause mortality, and to estimate the possible effect modification on 28-day all-cause mortality, in subgroups defined by source and site of infection, and baseline values of APACHE II score, MOD score and D-dimer. Conclusion: The available literature in animal and human research, and the understanding of the molecular biology regarding inflammation and coagulation, supports a randomized clinical trial for the use of heparin in sepsis. Our study will provide appropriate power to detect differences in valid surrogate outcomes, and it will explore important preliminary data for efficacy regarding the clinical end-point of mortality.